Physical decoloration in the concentration process of natural rubber. (26th May 2021) - Rojruthai, Porntip; Pareseecharoen, Chayaporn; Sakdapipanich, Jitladda
Abstract: Natural rubber (NR) latex contains many components, especially non‐rubber components, which can affect the color of products made from it. There is a growing demand in NR products which are lightly colored or color filled. One way to reduce the yellow color of NR is to remove non‐rubber components, for example, lipids and proteins, from NR. This study focused on several NR latex decoloration techniques, including controlling centrifugation speed and time as well as percentage of total solid content (% TSC) of field latex. It was found that the best condition to reduce yellow color was centrifugation of the field latex containing less than 35% TSC at 12, 000 rpm for 30 min. In addition, decoloration of NR latex was very effective by washing the centrifuged latex at least twice. Other factors, such as storage time and drying conditions, promoted coloration of NR due to the oxidation of the non‐rubbers. Abstract : ​